Penggunaan Metode Role Playing dalam meningkatkan Hasil Belajar Pendidikan Agama Islam Kelas VIII - Keis, Keis; Juhaeni, Juhaeni; Safaruddin, Safaruddin; Jannah, Ida Miftakhul; Salsabila, Zuha Prisma (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study used the Classroom Action Research (PTK) method with a two-cycle design and involved 31 students in class VIII SMP Negeri 1 Cipunagara. The purpose of this study was to improve student learning outcomes in Islamic Religious Education (PAI) subjects. Research data were collected using observation instruments, interviews, documentation, and formative tests. The results showed that in the pre-cycle, the average student learning outcomes were 69.12 with the level of achievement of Learning Objective Achievement Criteria (KKTP) 58.06%. After the application of the Role Playing method, there was a significant increase in cycle I, with a teacher activity score of 84, student activity of 75, and KKTP achievement increased to 64.51%. In cycle II, student learning outcomes increased more significantly with an average score of 89.19 and KKTP achievement of 90.32%. The teacher activity score also increased to 88.89, while student activity reached 87.50. This success is due to the active interaction of students, group discussions, and roles in learning scenarios that help students understand the material more deeply and applicatively. The conclusion in this study is that the Role Playing method is an effective learning strategy to improve PAI learning outcomes and instill character values.